Shifting Sensibilities : Architecture and the Aesthetics of the City - Lehtinen, Sanna (Scenari, 2021)
Aesthetic interest in architecture is a well-documented and discussed area of specialization in architectural philosophy. However, how it is related to the broader and so far, less-defined area of the aesthetics of the city is not equally clear. This article traces how aesthetics of the city is formulated based on architectural aesthetics but also through the notion of the human environment. The intention is to show, how aesthetic attention to architecture, building details, and analysis of the experience of architectural stylistic phenomena translates into a heightened awareness of the aesthetic dimensions of the urban lifeform. Whether explicitly or implicitly, the urban environment is interpreted based on information gained through the senses and we analyze and assess the city in the process continuously. This article presents some of the contemporary ideas developed within the aesthetics of architecture and the aesthetics of the city. The aim is to show a continuation from the aesthetic interest in the architectural form to the aesthetic interest which has the urban form in its focus. This is done through the notion of the human environment, which has been notably present in the philosophical study of environmental aesthetics. The article attempts to contribute to a growing body of literature defining urban aesthetics as a separate field of philosophical and applied environmental aesthetics.